Exhaust Particle Numbers of High- and Medium-Speed Diesel Engines with Renewable and Recycled Fuels - Ovaska, Teemu (My University, 2020)
The number of exhaust particles emitted from non-road diesel engines is regulated worldwide. This dissertation aimed to evaluate how different alternative fuels affect the exhaust particle number in high- and medium-speed engines. The fuels, all originating either from renewable or circular-economy feedstock, were used either neat or as blending components. Five experimental studies were performed in the laboratory, recording particle numbers within the size range of 5.6 to 560 nm. Circular-economy-based marine gas oil and a blend of renewable naphtha and light fuel oil reduced the exhaust total particle number in a medium-speed engine compared with neat light fuel oil. However, similarly produced marine gas oil and another blend of naphtha and light fuel oil did not lead to particle reductions in a high-speed engine. In another study with a high-speed engine, low-sulphur fossil diesel produced the lowest total particle number at most loads, while methyl esters of rapeseed and soy bean oil mostly reduced particles within a size range of 70 to 200 nm. In one high-speed engine study, increasing the share of renewable diesel in the fuel blend consistently reduced the exhaust particles. At low idle, neat renewable diesel reduced ultrafine particles significantly. A blend containing 20 vol.-% soy bean oil methyl ester in fossil diesel fuelled another high-speed engine in a 500-hour endurance test. The number of particles above 50 nm remained almost constant but finer particles increased. The probable reason seemed to be wear-out copper in the lubricant, not combustion degradation. As a whole, the results showed that alternative fuels originating either from renewable or circular-economy feedstock will not bring penalties in terms of number-based particle emissions in high- or medium-speed non-road engines.

Dieselmoottorien pakokaasun pienhiukkaslukumäärää säädellään maailmanlaajuisesti. Tämän väitöskirjan tavoitteena oli tutkia, miten uusiutuvat ja kierrätyspolttoaineet vaikuttavat nopea- ja keskinopeakäyntisten dieselmoottorien pakokaasun pienhiukkasten lukumäärään. Kierrätyspolttoaineen lisäksi selvitettiin uusiutuvien polttoaineiden sekä polttoaineiden seosten vaikutus. Tulokset perustuvat viiteen tutkimukseen, joissa pienhiukkaslukumäärä mitattiin laboratorio-olosuhteissa kokoalueella 5,6–560 nm. Sekä kierrätyspolttoaine että uusiutuvan naftan ja fossiilisen polttoaineen seos vähensivät keskinopeassa voimala- ja laivamoottorissa hiukkasten kokonaislukumäärää. Nopeakäyntisessä työkonedieselmoottorissa nämä polttoaineet eivät pienentäneet hiukkasmäärää. Yhdessä tutkimuksista nopeakäyntisen moottorin hiukkaslukumäärä oli pienin, kun ajettiin vähärikkisellä fossiilisella dieselpolttoaineella. Rypsi- ja soijapohjaiset metyyliesterit tuottivat kuitenkin yleensä vähiten hiukkasia välillä 70–200 nm. Toisessa tutkimuksessa saman moottorin kokonaishiukkaslukumäärä pieneni, kun seospolttoaineessa puuperäisen uusiutuvan dieselin määrä lisääntyi. Joutokäynnillä seostamaton uusiutuva diesel vähensi pienimpiä hiukkasia merkittävästi. Työkonemoottorin 500 tunnin pitkäaikaiskokeessa soijametyyliesterin (20 %) ja fossiilisen dieselöljyn seos ei juurikaan lisännyt yli 50 nm hiukkasia, mutta pienempien hiukkasten määrä nousi. Todennäköinen syy oli voiteluöljyssä havaittu kuparin lisääntyminen eikä seospolttoaineen palamiseen liittyvä tekijä. Kokonaisuudessaan tulokset osoittivat, että uusiutuvien ja kierrätyspolttoaineiden käyttö auttaa vähentämään nopea- ja keskinopeakäyntisten dieselmoottorien pienhiukkasten lukumääräpäästöä niin työkone- kuin voimala- ja laivamoottoreissakin.
Nopea- ja keskinopeakäyntisten dieselmoottorien pakokaasun pienhiukkaslukumäärä uusiutuvia ja kierrätyspolttoaineita käytettäessä
Keywords: diesel engine; exhaust; particle number; alternative fuels; fuels; diesel engines; diesel oil; exhaust gases; biofuels; fi=Energiatekniikka|en=Energy Technology|